Effect of 3D elliptical ultrasonic assisted boring on surface integrity. (15th October 2020) - Lotfi, Mohammad; Amini, Saeid; Aghayar, Zahra; Sajjady, Sayed Ali; Farid, Ali Akhavan
Highlights: 3D elliptical vibration method is represented to evaluate its effect on surface integrity in boring. 3D vibration reduces the depth of microstructure changes and improves surface microhardness. The feed-marks in conventional boring of Titanium are changed to micro-textures in vibratory method. 3D vibration eliminates the adhesion of working material which is happened in conventional one. Abstract: Improving surface integrity is an important issue to enhance wear resistance and fatigue life of the end product. Thus, a 3D elliptical vibration method is represented to evaluate its effect on the parameters of surface integrity in boring process. The operation is carried out on a titanium cylinder in two methods of conventional and 3D elliptical ultrasonic assisted boring. After the machining, surface roughness, microstructure changes, and microhardness of the cut surfaces are examined. The results show that 3D vibration causes the depth of microstructure changes to be less than conventional boring, while it increases the surface hardness, more. In addition, this method almost eliminates the effect of cutting parameters on surface roughness by producing micro-textures on the surface.